Bacterial community development and diversity during the first year of production in a new salmon processing plant. (February 2023) - Bjørge Thomassen, Gunn Merethe; Krych, Lukasz; Knøchel, Susanne; Mehli, Lisbeth
Abstract: The bacterial diversity and load on equipment in food processing facilities is constantly influenced by raw material, water, air, and staff. Despite regular cleaning and disinfection, some bacteria may persist and thereby potentially compromise food quality and safety. Little is known about how bacterial communities in a new food processing facility gradually establish themselves. Here, the development of bacterial communities in a newly opened salmon processing plant was studied from the first day and during the first year of operation. To focus on the persisting bacterial communities, surface sampling was done on strategical sampling points after cleaning and disinfection. To study the diversity dynamics, isolates from selected sampling and time points were classified by Oxford Nanopore Technology-based rep-PCR amplicon sequencing (ON-rep-seq) supplemented by 16S rRNA gene or rpoD gene sequencing (for Pseudomonas ). An overall increase in bacterial numbers was only observed for food-contact surfaces in the slaughter department, but not in filleting department, on non-food contact surfaces or on the fish. Changes in temporal and spatial diversity and community composition were observed and our approach revealed highly point-specific bacterial communities. Highlights: Pseudomonas is the most abundant genus on clean, disinfected food contact surfaces. ON-rep-seq provides species-level classification for most of the isolates analysed. Species/strain level classification of isolates reveal point-specific communities. Specific problematic spots for increased bacterial growth were localized.